Challenges and opportunities of novel imaging techniques in monoclonal plasma cell disorders: imaging “early myeloma” - Hillengaß, Jens; Landgren, Ola (Leukemia and lymphoma, 2013)
After decades of virtually no progress, multiple myeloma survival has improved significantly in the last 10 years. Indeed, multiple myeloma has perhaps seen more remarkable progress in treatment and patient outcomes than any other cancer during the last decade. Despite significant limitations, conventional radiological skeletal survey still remains the gold standard to rule out bone disease in patients with monoclonal plasma cell diseases. This is even more remarkable, as myeloma is actually a disease of the bone marrow and bone destruction is a secondary complication of advanced disease. Novel imaging techniques such as computed tomography (CT), magnetic resonance imaging (MRI) and positron emission tomography (PET) allow morphological and functional characterization including information on disease distribution (bone marrow, bone and extramedullary disease), disease activity and minimal residual disease after given therapy. The present review summarizes data on novel imaging techniques and discusses their clinical value and future opportunities for patients with monoclonal plasma cell diseases.